2018
DOI: 10.1093/icesjms/fsx237
|View full text |Cite
|
Sign up to set email alerts
|

Conflicts in the coastal zone: human impacts on commercially important fish species utilizing coastal habitat

Abstract: Coastal ecosystems are ecologically, culturally, and economically important, and hence are under pressure from diverse human activities. We reviewed the literature for existing evidence of effects of human-induced habitat changes on exploited fish utilizing coastal habitats. We focused on fish species of the Northeast Atlantic for which fisheries advice is provided by International Council for the Exploration of the Sea (ICES) and which utilize coastal habitats for at least one life-history stage (LHS). We fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 141 publications
2
41
0
Order By: Relevance
“…We relied on the authors of the original publications to supply information on such variables, but unfortunately these were not consistently reported enough to support rigorous analysis (see Supporting Information). A recent meta‐analysis also suggested that abiotic conditions can greatly influence the nursery function of coastal habitats (Igulu et al., ), and other reviews of nurseries along the Northeast Pacific (Hughes et al., ) and Northeast Atlantic coasts (Brown et al., ) found that numerous human‐induced stressors can pose a risk to the nursery function (Toft et al., ). To date, however, explicit examples of nursery impairment due to anthropogenic or other environmental factors are rare and should be considered as an important next step for nursery research.…”
Section: Discussionmentioning
confidence: 99%
“…We relied on the authors of the original publications to supply information on such variables, but unfortunately these were not consistently reported enough to support rigorous analysis (see Supporting Information). A recent meta‐analysis also suggested that abiotic conditions can greatly influence the nursery function of coastal habitats (Igulu et al., ), and other reviews of nurseries along the Northeast Pacific (Hughes et al., ) and Northeast Atlantic coasts (Brown et al., ) found that numerous human‐induced stressors can pose a risk to the nursery function (Toft et al., ). To date, however, explicit examples of nursery impairment due to anthropogenic or other environmental factors are rare and should be considered as an important next step for nursery research.…”
Section: Discussionmentioning
confidence: 99%
“…[59,64,91]) there is also the risk of inferring results from one or a few studies to support management decisions that may not deliver the desired results. The lack of evidence and the high heterogeneity that we show in this review point to the complexity of the issue and should motivate more investment in targeted research towards evaluating the value of coastal habitats [16], impacts of human activities on these habitats [116] and finally link the pressures (coastal habitat reconstruction) with fish recruitment. Only then can managers implement evidence-based regulations of human activities, mitigate effects, and execute compensatory actions for these activities.…”
Section: Implications For Policy and Managementmentioning
confidence: 97%
“…Habitat alteration and loss are continuing in coastal zones due to accelerating human development (Lotze et al, 2006;Airoldi and Beck, 2007). Many fish and invertebrate species rely on coastal habitats for one or more of their life stages (Seitz et al, 2014;Vasconcelos et al, 2014;Brown et al, 2018); thus, there will be increasing demands for models that can be used to quantify how changes in habitat will affect these populations. We use our review as the basis of the following recommendations and comments about the incorporation of habitat in population modeling of coastal and marine fish and shellfish.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%